A neural-enhanced active disturbance load-side speed control of an electric drive with a flexible link - Kaczmarczyk, Grzegorz; Stanislawski, Radoslaw; Kaminski, Marcin; Kasprzak, Kacper; Ferreira, Danton Diego (Archives of Electrical Engineering (Online), 2025)
The paper is focused on improvements of the conventional speed controller based on Active Disturbance Rejection Control (ADRC) applied for a two-mass electric drive system. The described ADRC structure is based on load-side speed measurement. The paper compares conventional structure dynamics with overall system behavior in the case plant parameters are changed. The proposed ADRC algorithm extension performs soft controller parameters adjustment to improve the dynamics and plant response. The presented approach accomplishes adaptation capabilities with the use of a Radial Basis Function Neural Network (RBFNN). The article presents the dynamic response of the plant controlled by the conventional ADRC algorithm and the designed neural adaptation extension. The results are based on the performed experimental tests.